Formalization of communal land tenure and expectations for pastoralist livelihoods. (March 2022) - Senda, Trinity S.; Robinson, Lance W.; Gachene, Charles K.K.; Kironchi, Geoffrey
Abstract: Despite progress towards recognizing communal land rights, there may be unintended outcomes, and for pastoral areas there is a need to be aware of how this may affect evolving pastoralist livelihoods. This paper examines trends in pastoralist livelihoods, perceptions and aspirations of pastoralists in a setting where a new communal property rights framework is in the early stages of implementation. The study was carried out in Dirre, a grazing unit of the Borana Zone in Ethiopia. It employed a mixed methods approach that included key informant interviews, focus group discussions, a workshop, a household survey and feedback sessions. The findings show that current livestock herd sizes make it difficult for pastoralists to rely only on livestock keeping, and have necessitated diversification. Crop production is increasingly becoming an alternative livelihood source, and most respondents reported wanting to expand their farms. Pastoralists also expect land certification to help secure land rights and enable better management of rangelands. However, there is also a widely held view that by providing security, certification will also make it easier for them to continue diversifying their livelihoods. This suggests that communal land certification is not likely to end the push to individualization of land and the transition to agropastoralism; it may even accelerate it. The strengthening of communal land rights can thus be used to guide this transition so that it represents a reorganization rather than a collapse of pastoralism. The focus of formalizing land rights for pastoralists should not be saving pastoralism or reversing the agropastoralist trend, but rather securing land rights to enhance the pastoralists' capacity to make sound livelihood decisions. Highlights: The focus of land certification should be to enhance the pastoralists' capacity to make sound livelihood decisions. Formalization of communal land rights is expected enable better management of common pool rangelands. Declining herd sizes make it difficult to rely solely on livestock, hence the push to diversify into other livelihood options. Pastoralists are willing to invest meaningfully in cropping if they are tenure secure. Land certification is not likely to end the push to individualization and the shift to agropastoralism; it may accelerate it.